2015
DOI: 10.1371/journal.pone.0145860
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Mycobacterium tuberculosis Isolates from Assam, India: Dominance of Beijing Family and Discovery of Two New Clades Related to CAS1_Delhi and EAI Family Based on Spoligotyping and MIRU-VNTR Typing

Abstract: Tuberculosis (TB) is one of the major public health concerns in Assam, a remote state located in the northeastern (NE) region of India. The present study was undertaken to explore the circulating genotypes of Mycobacterium tuberculosis complex (MTBC) in this region. A total of 189 MTBC strains were collected from smear positive pulmonary tuberculosis cases from different designated microscopy centres (DMC) from various localities of Assam. All MTBC isolates were cultured on Lowenstein-Jensen (LJ) media and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 63 publications
8
22
1
Order By: Relevance
“…In particular, the five East Asian (L2) PCR00002 clusters had significantly decreased odds of epidemiologic linkages using GENType (OR=0.05, 95% CI 0.001, 0.95) and were heterogeneous both by birth country and MIRU24; only 26% (10/38) of patients clustered by GENType, which was significantly less than patients in other clusters (272/304, 90%, p<0.001). These findings appear to be consistent with the insufficient discrimination power of MIRU24 in isolates from the Beijing family that were reported by other authors [2223]. …”
Section: Discussionsupporting
confidence: 93%
“…In particular, the five East Asian (L2) PCR00002 clusters had significantly decreased odds of epidemiologic linkages using GENType (OR=0.05, 95% CI 0.001, 0.95) and were heterogeneous both by birth country and MIRU24; only 26% (10/38) of patients clustered by GENType, which was significantly less than patients in other clusters (272/304, 90%, p<0.001). These findings appear to be consistent with the insufficient discrimination power of MIRU24 in isolates from the Beijing family that were reported by other authors [2223]. …”
Section: Discussionsupporting
confidence: 93%
“…People from Dharana city in eastern Nepal used to frequently travel to Hong Kong, China to work as members of the British Gurkha Army 24 . There is still frequent movement of people between the eastern region of Nepal and north-eastern parts of India where the Beijing family is dominant 25 . Since, MTB is suggested to have co-expanded in line with human migration 26 , these phenomena might explain the establishment of the Beijing family in eastern and central region and might be one of reasons for the higher chance of isolating the Beijing family in eastern Nepal (Tables 4 – 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, Sahariya tribe has been most widely studied in context of TB prevalence, genetic susceptibility to TB and associated risk factors [41]. But, the [7,17] The present study revealed EAI3_IND/SIT11 as one of the major genotypes in Sahariya tribe followed by CAS1_Delhi/SIT26 while in non-tribes, EAI3_IND/SIT11 and CAS1_Delhi/SIT26 both genotypes were observed to a similar degree. A 3.04 fold higher risk of infection with EAI3_IND/SIT11 genotype was observed in Sahariya tribe as compared to non-tribes.…”
Section: Discussionmentioning
confidence: 39%
“…Molecular typing has always facilitated in population based monitoring of TB control programmes and understanding the TB epidemics [13]. The most commonly used tools for molecular epidemiological investigations are IS6110-RFLP typing, spoligotyping and MIRU-VNTR typing [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. These markers have been demonstrated successfully in studying micro-evolutionary changes and mixed strain infections in MTB strains [29,30].…”
Section: Introductionmentioning
confidence: 99%